Perlindungan Hukum Terhadap Pemilik Tanah Hak Eigendom Yang Dikuasai Oleh Pemerintah Dengan Sertifikat Hak Pakai - Permadi, Iwan; Bayu Setiawan, Endrianto (Fakultas Hukum Universitas Islam Malang, 2024)
Holders of eigendom rights under Law No. 5/1960 on Basic Agrarian Principles are required to apply for and grant new rights to land derived from the conversion of western rights within 20 years. Then there is a land dispute between the previous landowner and the government who controls the land with a right of use certificate. This research is a normative research using statutory approach, conceptual approach, historical approach, and comparative approach. Land with the status of eigendom rights that have not been converted can still be converted into property rights as long as the applicant is still the holder of the land rights in the old evidence or has not been transferred to the name of another person and there is a map / measurement letter, as well as legal protection for eigendom rights holders who are converted into land rights in the form of property rights certificates.